Welding of AA1050 aluminum with AISI 304 stainless steel by rotary friction welding process - Alves,Eder Paduan (2010)
Abstract: The purpose of this work was to assess the development of solid state joints of dissimilar material AA1050 aluminum and AISI 304 stainless steel, which can be used in pipes of tanks of liquid propellants and other components of the Satellite Launch Vehicle. The joints were obtained by rotary friction welding process (RFW), which combines the heat generated from friction between two surfaces and plastic deformation. Tests were conducted with different welding process parameters. The results were analyzed by means of tensile tests, Vickers microhardness, metallographic tests and SEM-EDX. The strength of the joints varied with increasing friction time and the use of different pressure values. Joints were obtained with superior mechanical properties of the AA1050 aluminum, with fracture occurring in the aluminum away from the bonding interface. The analysis by EDX at the interface of the junction showed that interdiffusion occurs between the main chemical components of the materials involved. The RFW proves to be a great method for obtaining joints between dissimilar materials, which is not possible by fusion welding processes.